Mechanism of Plantamajoside in inhibiting ferroptosis of pancreatic β cells and treatment of T2DM via activation of the xCT/GPX4 pathway - Hongmin Zhao; Renlin Li; Xuan Guo; Jingrui Kang; Huajun Li; Xiaoyun Wang; Yuansong Wang; Huantian Cui; Shuquan Lv; Weibo Wen; Zhongyong Zhang (PLoS ONE, 2025)
Pancreatic β-cell damage, a key pathology in Type 2 Diabetes Mellitus (T2DM), may be mitigated by inhibiting ferroptosis. Plantamajoside (PMS) shows promise in alleviating cellular damage and improving T2DM outcomes, though its mechanisms remain unclear. This study investigated PMS’s role in suppressing ferroptosis in pancreatic β-cells via the cysteine/glutamate transporter (xCT)/ glutathione peroxidase 4 (GPX4) pathway. In our in vivo experiments, PMS was administered to T2DM mice via gavage, and its effects on tissue damage, ferroptosis, and xCT/GPX4 pathway modulation were assessed. Furthermore, in vitro experiments employed high glucose (HG) and palmitic acid (PA) conditions, to induce damage in pancreatic β-cells. We investigated the beneficial impacts of PMS on pancreatic β-cell damage, its modulation of ferroptosis, and its influence on the xCT/GPX4 pathway. To compare the capacity of PMS to inhibit ferroptosis, we utilized the ferroptosis inhibitor ferrostatin-1 (Fer-1) as a positive control, while the GPX4 inhibitor RSL-3 validated PMS’s mechanism through the xCT/GPX4 axis. Our findings revealed that PMS effectively mitigated pancreatic tissue damage in T2DM mice, reduced ferroptosis, and enhanced the expression of factors associated with the xCT/GPX4 pathway. Moreover, PMS alleviated HG and PA-induced damage in pancreatic β-cells, suppressed ferroptosis, and upregulated factors linked to the xCT/GPX4 pathway. Similar to the ferroptosis inhibitor Fer-1, PMS exhibited comparable effects. Conversely, RSL-3 attenuated the protective effects of PMS on pancreatic β-cell damage, its inhibition of ferroptosis, and its activation of the xCT/GPX4 pathway. PMS exhibited the capacity to diminish damage to pancreatic islet β-cells induced by T2DM, both in vivo and in vitro. This favorable outcome may stem from the alleviation of lipid peroxidation and reduction of ferroptosis. Moreover, this regulatory mechanism was accomplished through the enhancement of the xCT/GPX4 axis.